The formation of political discourse within online networks: the case of the occupy movement. (1st January 2014) - Fábrega, Jorge; Sajuria, Javier
How does political discourse spread in digital networks? Can we empirically test if certain conceptual frames of social movements have a correlate on their online discussion networks? Through an analysis of Twitter data from the occupy movement, this paper describes the formation of political discourse over time. Building on an a priori set of concepts, derived from theoretical discussions about the movement and its roots, we analyse the data to observe when those concepts start to appear within the networks, who are those Twitter users responsible for them, and what are the patterns through which those concepts spread. Our findings show that, although there are some signs of opportunistic behaviour among activists, most of them are central nodes from the onset of the network, and shape the discussions across time. These central activists do not only start the conversations around given frames, but also sustain over time and become key members of the network. From here, we aim to provide a thorough account of the 'travel' of political discourse, and the correlate of online conversational networks with theoretical accounts of the movement.